The Influence of the Contextual Teaching and Learning (CTL) Model on Improving Critical Thinking Skills in Mathematics among Junior High School Students - Arum Iriley Mallika (Institute of Accounting Research and Novation (IARN), 2024)
This study investigates the impact of the Contextual Teaching and Learning (CTL) model on improving critical thinking skills in junior high school students, specifically in mathematics education. The research adopts a quasi-experimental design, involving two groups: an experimental group exposed to the CTL model and a control group receiving traditional mathematics instruction. The study was conducted in a junior high school, and data were collected through pre- and post-tests assessing students' critical thinking abilities in mathematics. The findings reveal that students in the experimental group demonstrated significant improvements in critical thinking skills compared to the control group. These improvements were evident in their ability to analyze mathematical problems, make logical connections, and apply mathematical concepts to real-world situations. The study concludes that the CTL model, by integrating real-life contexts into mathematics instruction, fosters a deeper understanding of mathematical concepts and enhances students’ higher-order thinking abilities. The research supports the use of student-centered, contextual learning approaches as an effective strategy for improving critical thinking in mathematics education at the junior high school level.